Dissociation of enzymatic and pharmacological properties of piratoxins-I and -III, two myotoxic phospholipases A(2) from Bothrops pirajai snake venom - Soares, A. M.; Andriao-Escarso, S. H.; Bortoleto, R. K.; Rodrigues-Simioni, L.; Arni, R. K.; Ward, R. J.; Gutierrez, J. M.; Giglio, JR (Academic Press Inc., 2001)
Piratoxins (PrTX) I and III are phospholipases A(2) (PLA(2)s) or PLA(2) homologue myotoxins isolated from Bothrops pirajai snake venom, which also induce myonecrosis, bactericidal activity against Escherichia coli, disruption of artificial membranes, and edema. PrTX-III is a catalytically active hemolytic and anticoagulant Asp49 PLA(2), while PrTX-I is a Lys49 PLA, homologue, which is catalytically inactive on artificial substrates, but promotes blockade of neuromuscular transmission. Chemical modifications of His, Lys, Tyr, and Trp residues of PrTX-I and PrTX-III were performed, together with cleavage of the N-terminal octapeptide by CNBr and inhibition by heparin and EDTA. The lethality, bactericidal activity, myotoxicity, neuromuscular effect, edema inducing effect, catalytic and anticoagulant activities, and the liposome-disruptive activity of the modified toxins were evaluated. A complex pattern of functional differences between the modified and native toxins was observed. However, in general, chemical modifications that significantly affected the diverse pharmacological effects of the toxins did not influence catalytic or membrane disrupting activities. Analysis of structural changes by circular dichroism spectroscopy demonstrated significant changes in the secondary structure only in the case of N-terminal octapeptide cleavage. These data indicate that PrTX-I and PrTX-III possess regions other than the catalytic site, which determine their toxic and pharmacological activities. (C) 2001 Academic Press.
Keywords: Bothrops pirajai; myotoxins; phospholipase A(2); pharmacological activities; chemical modifications; Circular dichroism; Crystal structure